2012
DOI: 10.1002/joc.3454
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of acid‐coated ice nuclei on the Arctic cloud microstructure, atmospheric dehydration, radiation and temperature during winter

Abstract: ABSTRACT:Owing to the large-scale transport of pollution-derived aerosols from the mid-latitudes to the Arctic, most of the aerosols are coated with acidic sulfate during winter in the Arctic. Recent laboratory experiments have shown that acid coating on dust particles substantially reduces the ability of these particles to nucleate ice crystals. Simulations performed using the Limited Area version of the Global Multiscale Environmental Model (GEM-LAM) are used to assess the potential effect of acid-coated ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 55 publications
4
36
1
Order By: Relevance
“…The DGF impact of the TIC2 particles (meaning their progressive removal by precipitation) would accordingly be that their radiative forcing influence would progressively decrease with an attendant cooling due to a reduction in thermal interaction with the remaining TIC1 particles (and the unprecipitated TIC2 particles). A long-term analysis would help to support modeling conclusions on the impact of acid-coated ice nuclei on Arctic cloud as reported by Girard et al (2013). These authors reported Radiometer TIC1 6 9 TIC2 1 68 Overall accuracy = 88 % err.…”
Section: Validation Of Our Retrieval Algorithmmentioning
confidence: 68%
“…The DGF impact of the TIC2 particles (meaning their progressive removal by precipitation) would accordingly be that their radiative forcing influence would progressively decrease with an attendant cooling due to a reduction in thermal interaction with the remaining TIC1 particles (and the unprecipitated TIC2 particles). A long-term analysis would help to support modeling conclusions on the impact of acid-coated ice nuclei on Arctic cloud as reported by Girard et al (2013). These authors reported Radiometer TIC1 6 9 TIC2 1 68 Overall accuracy = 88 % err.…”
Section: Validation Of Our Retrieval Algorithmmentioning
confidence: 68%
“…The ice crystal growth rate in very cold conditions impinges on the precipitation efficiency, dehydration and radiation balance. A regional climate model evaluating the impact of the IN deactivation effect by acid coating on the cloud microstructure, precipitation and radiation have also been performed by Girard et al (2013). Results show that acid coating on dust particles has an important effect on cloud microstructure, atmospheric dehydration, radiation and temperature over the Central Arctic, which is the coldest part of the Arctic.…”
Section: Discussionmentioning
confidence: 99%
“…No modifications have been made to the original scheme for the parameterization of contact freezing. Deposition ice nucleation on uncoated IN and immersion freezing of sulphuric acid-coated IN are parameterized following Girard et al (2013). These parameterizations are based on the classical nucleation theory (CNT) of Fletcher (1962).…”
Section: Model Descriptionmentioning
confidence: 99%
“…1) and their spatial and temporal variabilities. Following Girard et al (2013), a constant value in time and space (0.38 cm -3 ) for N dust is assumed since the model does not simulate aerosol transport and physics. This means that there are no sources and sinks of dust particles.…”
Section: Numerical Configurationmentioning
confidence: 99%
See 1 more Smart Citation